Mercury emissions inventory for 2014 in Costa Rica using the PNUMA Toolkit to a N2 level - Murillo-Hernández, Julio César (2017)
The Minamata Convention was signed in October 2013 to protect human health and the environment from releases and anthropogenic emissions of elemental mercury and compounds containing this element.  When Costa Rica ratified this instrument, the country committed to develop and keep updated an inventory of emissions from the relevant sources of mercury. In the present work, the tool proposed by UNEP was used to generate the first mercury inventory at the N2 level of the country, which considers releases of mercury in air, water, soil, product and waste matrices. Taking 2014 as the reference year, the estimated mercury emission for Costa Rica was recorded at 5 052 kg, with an uncertainty interval between 2 675 kg and 10 525 kg; and the most important sectors in terms of the total emission were the extraction of gold with amalgamation (42 %), informal burning of waste (15 %) and use of dental amalgams (10 %). The most impacted matrices were air (29 %), water (28 %) and soil (21 %), respectively.